Small States : Performance in Public Debt Management - Prasad, Abha; Pollock, Malvina; Li, Ying (World Bank, Washington, DC, 2013)
This paper analyzes the status of public debt management performance in 17 small states through the findings of the Debt Management Performance Assessment reports. Empirical evidence indicates that the higher the quality of a country's policies and institutions, the better is its capacity to carry debt and withstand exogenous shocks. Borrowing for productive purposes can be an important element in boosting growth of gross domestic product but, conversely, excessive borrowing or poorly structured debt in terms of maturity, currency, or interest rate composition can quickly offset the positive impact, deter new foreign and domestic investment, compromise reform programs, depress growth of gross domestic product, exacerbate the challenge of meeting debt service obligations, and may induce or propagate economic crises. Arguments in favor of sound debt management are especially compelling for small states that must mitigate the particular risks to which their economies are exposed. Against this backdrop, the paper identifies aspects of debt management where small states do relatively well and those where they perform poorly, relative to other developing countries, and examines the underlying factors at play. It elaborates on some of the successful measures taken by small states to enhance debt management performance and considers how these may be applied more broadly in other small states. The paper offers a number of practical suggestions to strengthen debt management performance.